Analsis Kelayakan Isi Buku Ajar Mata Pelajaran Fiqih Kelas VII MTs Yayasan Pendidikan Az-Zuhri - Muhammad Rosidin (Yayasan Rahmat Islamiyah, 2022)
This journal discusses an important problem that is often faced in learning activities is choosing the right textbook in order to help students achieve competence. This study aims to determine the background of the selection of fiqh textbooks and the quality of the seventh grade fiqh textbooks at MTs Yayasan Pendidikan Az-Zuhri. This research is a type of qualitative research, while the research method carried out in data analysis using the content analysis method is a research technique to make inferences that can be replicated and valid data by taking into account the context. The results showed that first, the selection of fiqh textbooks at MTs Az-Zuhri Education Foundation was more consistent with using the Mawaridussalam Press publisher. The quality of the textbooks used at the Az-Zuhri Education Foundation MTs is considered poor because, in presenting the content of the material as a whole, it is not in accordance with the SK and KD, in terms of presentation it does not meet the completeness of the presentation and does not contain a complete list of supporters, in terms of language the lack of conformity with the level of development of students, and in terms of graphics there are still many that are not in accordance with the aspects of quality textbooks. However, it requires a review of the National Education Standards Agency (BSNP) in order to produce a book of better quality in terms of the aspects of the book.